MENYELISIK POSISI SYIAH DI DALAM ISLAM - Assa Dullah Rouf; Nunu Burhanuddin (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
This article delves into the intricate position of Shia in Islam, exploring the differences between the Sunni and Shia sects, along with the internal sects within Shia. It examines the significant potential of both major sects, hindered, unfortunately, by prolonged conflicts. The primary focus of the article is the exploration of Shia perspectives on leadership and caliphate, with an emphasis on the differing concepts of imamate among Shia sects, including moderate and extreme factions. The research methodology employs a literature review approach with a critical descriptive analysis, gathering data from various sources to support the analysis. The article yields a deeper understanding of the evolution of thought within the Shia sect over time. The results and discussions highlight the importance of comprehending the internal variations within Shia before making negative generalizations. The article asserts that generalizations about Shia can be detrimental, emphasizing the need for a more profound understanding to avoid misconceptions. Ultimately, the article proposes the significance of respecting diverse viewpoints, prioritizing positive assumptions, and seeking common ground between Sunni and Shia within the context of the unity of the Muslim community. In conclusion, this article provides comprehensive insights into the position of Shia in Islam, stimulating contemplation on the unity of the Muslim community and emphasizing the urgency of further research to deepen understanding of diverse Islamic sects